Radiation effects in semiconductor scintillators based on zinc selenide - Ryzhikov, V.; Koshkin, V.; Starzhinskiy, N.; Ibragimova, E.; Gafarov, A.; Kist, A.; Oksengendler, B.; Gal’chinetskii, L.; Katrunov, K.; Galkin, S.; Silin, V. (Вопросы атомной науки и техники, 2003)
Effects have been studied of gamma-radiation (Еγ=1.25 МeV) in doses of DγЈ5.10⁹ rad upon light output and spectral-kinetic luminescence characteristics of new semiconductor scintillators (SCS) based on isovalently doped (with tellurium and oxygen) zinc selenide crystals. SCS crystals have been shown to be of extremely high radiation stability, and changes in their optical and luminescent properties became noticeable only under doses Dγ>(7.9).10⁷ rad. Under gamma-irradiation with Dγ>(2-5).10⁹ rad and Pγ=7.7.10² R.s⁻¹, in the surface layer (estimated in tens of nanometers) radiolysis of the crystalline structure occurs, and the loss of mass is observed for the samples (at Т=320 К). Mechanisms are considered that describes variation of SCS properties under powerful radiation fluxes.